2019
DOI: 10.32598/bcn.9.10.330
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Learning and Memory in Barnes Maze Test and Synaptic Potentiation in Schaffer Collateral-CA1 Synapses of Dorsal Hippocampus in Freely Moving Rats

Abstract: Synaptic plasticity has been suggested as the primary physiological mechanism underlying memory formation. Many experimental approaches have been used to investigate whether the mechanisms underlying Long-Term Potentiation (LTP) are activated during learning. Nevertheless, little evidence states that hippocampal-dependent learning triggers synaptic plasticity. In this study, we investigated if learning and memory in the Barnes maze test are accompanied by the occurrence of LTP in Schaffer collateral to CA1 syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…We next assessed phenotypic modifications of astrocytes ( Figure 3 b,c) and microglia ( Figure 4 ). We quantified the density of the astrocytes population (GFAP+ cells) within the hippocampal CA1 region, a brain area involved in synaptic plasticity and spatial memory mechanisms [ 37 ] ( Figure 3 b,c). We first observed that astrocyte density was considerably lower (by 40%) in WSB/EiJ CA1 than in C57BL/6J strain (Strain effect p = 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…We next assessed phenotypic modifications of astrocytes ( Figure 3 b,c) and microglia ( Figure 4 ). We quantified the density of the astrocytes population (GFAP+ cells) within the hippocampal CA1 region, a brain area involved in synaptic plasticity and spatial memory mechanisms [ 37 ] ( Figure 3 b,c). We first observed that astrocyte density was considerably lower (by 40%) in WSB/EiJ CA1 than in C57BL/6J strain (Strain effect p = 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Despite similar search strategies and learning outcomes, there was evidence of sex-specific effects of running on reversal learning on the Barnes maze. The non-spatial serial search strategy (Video S1) is not uncommon in Sprague-Dawley rats [128] that have lower visual acuity than other strains (e.g., Long-Evans and Wistar) [128,132] where using a serial search strategy may be more efficient. Notably, the increase in errors made from the probe to reversal learning trials was higher in WR females compared to their Sed counterparts, whereas there was no such group difference in males.…”
Section: Discussionmentioning
confidence: 99%
“…Synapses are specialized junctions between neurons in the brain that transmit and compute information, thereby connecting neurons into millions of overlapping and interdigitated neural circuits 50 . Synaptic plasticity has been suggested as the primary physiological mechanism underlying memory formation 51 . Abnormal synaptic structure or function in childhood can lead to dysfunction of the central nervous system, which is manifested as a decrease in learning and memory abilities and mental deficiency 52 .…”
Section: Discussionmentioning
confidence: 99%
“…50 Synaptic plasticity has been suggested as the primary physiological mechanism underlying memory formation. 51 Abnormal synaptic structure or function in childhood can lead to dysfunction of the central nervous system, which is manifested as a decrease in learning and memory abilities and mental deficiency. 52 In contrast to the results of a previous report that showed no significant alterations in the synapses, 41 we found that the synapses of rats became shorter and thicker in the high-dose PQ + MB treatment group, showing serious dysfunction of the central nervous system.…”
Section: Adolescent Exposure To Pq + Mb Decreased the Hippocampal Amentioning
confidence: 99%